Prediction of Skin Sensitization Potential of Silver and Zinc Oxide Nanoparticles Through the Human Cell Line Activation Test - Gautam, Ravi; Yang, SuJeong; Maharjan, Anju; Jo, JiHun; Acharya, Manju; Heo, Yong; Kim, ChangYul (Frontiers in Toxicology, 2021)
The development of nanotechnology has propagated the use of nanoparticles (NPs) in various fields including industry, agriculture, engineering, cosmetics, or medicine. The use of nanoparticles in cosmetics and dermal-based products is increasing owing to their higher surface area and unique physiochemical properties. Silver (Ag) NPs’ excellent broad-spectrum antibacterial property and zinc oxide (ZnO) NPs’ ability to confer better ultraviolet (UV) protection has led to their maximal use in cosmetics and dermal products. While the consideration for use of nanoparticles is increasing, concerns have been raised regarding their potential negative impacts. Although used in various dermal products, Ag and ZnO NPs’ skin sensitization (SS) potential has not been well investigated using in vitro alternative test methods. The human Cell Line Activation Test (h-CLAT) that evaluates the ability of chemicals to upregulate the expression of CD86 and CD54 in THP-1 cell line was used to assess the skin sensitizing potential of these NPs. The h-CLAT assay was conducted following OECD TG 442E. NPs inducing relative fluorescence intensity of CD86 ≥ 150% and/or CD54 ≥ 200% in at least two out of three independent runs were predicted to be positive. Thus, Ag (20 nm, 50 nm, and 80 nm) NPs and ZnO NPs were all predicted to be positive in terms of SS possibility using the h-CLAT prediction model. Although further confirmatory tests addressing other key events (KEs) of SS adverse outcome pathway (AOP) should be carried out, this study gave an insight into the need for cautious use of Ag and ZnO NPs based skincare or dermal products owing to their probable skin sensitizing potency.